Pengaruh Motivasi Kerja dan Kepuasan Kerja terhadap Kinerja Guru dan Pegawai di SMA Negeri 1 Deli Tua - Kariana Br Tarigan; Habil Ikhwana; Riny Viri Insy Sinaga (ProBank, 2025)
Developing human resources intellectually, spiritually, creatively, ethically, and responsibly is a path that Indonesians can take to participate in the global arena. The importance of quality education is integral to improving the quality of resources themselves. Human capital is the main capital in building and developing the national economy. This study aims to determine the effect of work motivation and job satisfaction, partially and simultaneously, on the performance of teachers and employees at SMA Negeri 1 Deli Tua. This research was conducted at a public school in Medan City using a quantitative approach and a saturated sample size of 80 respondents. Regression analysis was used to process and interpret the data using IBM SPSS Version 25. Work motivation and job satisfaction have a significant influence on the performance of teachers and employees at SMA Negeri 1 Deli Tua, both simultaneously and partially, with a contribution of 62.4 percent.